Ship construction - Eyres, David J. (Elsevier, 2001)
"Acting as both a professional reference on current approaches in shipyard practice and a comprehensive introduction for students in any marine discipline, Ship Construction covers the complete construction process, from ship specification to completed vessel." -- Page 4 of cover.